P(a)−P(b) = a^n(a^n-b^n)+a^n - 1(a^n-1−b^n−1)+...+a^1(a−b) = (a−b)x

How does the RHS come about? I'm not quite sure. I'm looking at a line of proof and can't quite make the connection.

this is given that P(a)=b P(b)=c P(c)=a.

Printable View

- August 10th 2012, 11:54 PMIdiotinaboxHow does this result come about?
P(a)−P(b) = a^n(a^n-b^n)+a^n - 1(a^n-1−b^n−1)+...+a^1(a−b) = (a−b)x

How does the RHS come about? I'm not quite sure. I'm looking at a line of proof and can't quite make the connection.

this is given that P(a)=b P(b)=c P(c)=a. - August 10th 2012, 11:56 PMProve ItRe: How does this result come about?
- August 11th 2012, 12:05 AMIdiotinaboxRe: How does this result come about?
http://www.math.ucsb.edu/mathclub/Pr...6Prob3FSol.pdf is the solution. Second line of proof. Sorry, forgot to include that x belongs to set of integer numbers